Bipolar vessel sealing: instrument contamination and wear have little effect on seal quality and success in a porcine in vitro model - Wallwiener, Christian Wilhelm; Junginger, Susanna H.; Zubke, Wolfgang; Brucker, Sara Y.; Enderle, Markus D.; Neugebauer, Alexander; Schönfisch, Birgitt; Wallwiener, Markus (Langenbeck's archives of surgery, 2014)
The aim of this study is to systematically investigate under standardized experimental conditions the effects of instrument contamination and wear on the quality of bipolar vessel sealing (BVS) achieved using a reusable instrument.